2014
DOI: 10.1155/2014/869148
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Protect Fine Particulate Matter-Induced Inflammatory Responses in Human Umbilical Vein Endothelial Cells

Abstract: Objective. To investigate the role of CD4+CD25+ T cells (Tregs) in protecting fine particulate matter (PM-) induced inflammatory responses, and its potential mechanisms. Methods. Human umbilical vein endothelial cells (HUVECs) were treated with graded concentrations (2, 5, 10, 20, and 40 µg/cm2) of suspension of fine particles for 24h. For coculture experiment, HUVECs were incubated alone, with CD4+CD25− T cells (Teff), or with Tregs in the presence of anti-CD3 monoclonal antibodies for 48 hours, and then were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
2
8
0
1
Order By: Relevance
“…Interestingly, local and systemic inflammation in Rag1 −/− mice resembled that of wild type mice, indicating that T- and B-lymphocytes do not play a relevant role in this context. On the contrary, we observed that some cytokine levels were even higher in Rag1 −/− than in wild type mice, suggesting a protective role of some lymphocyte subsets, as previously suggested for T-regulatory cells in lung inflammation [ 54 ]. Specific depletion of alveolar macrophages reduced local and systemic inflammation after ROFA exposure, indicating that alveolar macrophages are the source of circulating pro-inflammatory cytokines in our model.…”
Section: Discussionsupporting
confidence: 60%
“…Interestingly, local and systemic inflammation in Rag1 −/− mice resembled that of wild type mice, indicating that T- and B-lymphocytes do not play a relevant role in this context. On the contrary, we observed that some cytokine levels were even higher in Rag1 −/− than in wild type mice, suggesting a protective role of some lymphocyte subsets, as previously suggested for T-regulatory cells in lung inflammation [ 54 ]. Specific depletion of alveolar macrophages reduced local and systemic inflammation after ROFA exposure, indicating that alveolar macrophages are the source of circulating pro-inflammatory cytokines in our model.…”
Section: Discussionsupporting
confidence: 60%
“…Direct interactions between Tregs and endothelial cells have been reported previously using co-cultures of human umbilical vein endothelial cells and Tregs. Tregs inhibited pro-inflammatory responses in endothelial cells exposed to lipopolysaccharide, oxidized low-density lipoprotein or particulate matter, by downregulating adhesion molecules and reducing inflammatory cytokines (Li et al, 2011;Zhang et al, 2014a). These studies suggest that both direct cellcell contacts and soluble factors from Tregs (IL-10 and TGF-b1) may mediate Treg-endothelial cell interactions.…”
Section: Discussionmentioning
confidence: 73%
“…The microvascular accumulation of these immune cells and their secreted factors disrupts the adhesions between endothelial cells and degrades the extracellular matrix, resulting in irreversible BBB disruption. tPA treatment has been shown to exacerbate post-stroke inflammation in the microvasculature through multiple mechanisms, including the induction of MMP activity and the enhancement of leucocyte infiltration (Lapchak et al, 2000;Montaner et al, 2003;Wang et al, 2003Wang et al, , 2004Wang et al, , 2014Cheng et al, 2006;Copin et al, 2011). These mechanisms all contribute to the rupture of the BBB and lead to lethal haemorrhages in the ischaemic brain.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms may also underlie the Treg-associated BBB protection. Studies with human umbilical vein ECs demonstrate that direct Treg-EC contact and soluble factors are required for Treg-mediated suppression of EC inflammation (Zhang et al, 2014). Further investigation using brain ECs is warranted.…”
Section: Mechanisms Of Blood-brain Barrier Dysfunction After Ischementioning
confidence: 99%